Polarization and Demonization in the 2018 Presidential Campaign of Colombia: Analysis of Twitter’s Communication Behavior by Gustavo Petro and Iván Duque - Prada Espinel, Oscar Andrés (2018)
This research aims to analyze political communication through Twitter during the presidential election campaign in Colombia in 2018, since this digital platform has become an essential tool to generate an approchement with the citizenship and express the fundamental basis of its action plan if elected. Based on a qualitative-quantitative, descriptive and correlational design research, the accounts of Gustavo Petro (@petrogustavo) and Iván Duque (@IvanDuque) were analyzed during the month prior to the first round and the 21st days before the second round in the electoral process. To do this, the number of followers who held these profiles was examined and what were the topics in the contents that the candidates emphasized.